Analysis of Structuralism and Religious Values in the Short Story Pengemis dan Shalawat Badar in the Anthology Short Story of Senyum Karyamin by Ahmad Tohari - Wasniah Wasniah; Yulianeta Yulianeta (MASI Mandiri Edukasi, 2022)
This study aims to determine structuralism and religious values in the short story